2019
DOI: 10.3389/fevo.2019.00103
|View full text |Cite
|
Sign up to set email alerts
|

A Network Perspective for Community Assembly

Abstract: Species interactions are responsible for many key mechanisms that govern the dynamics of ecological communities. Variation in the way interactions are organized among species results in different network structures, which translates into a community's ability to resist collapse and change. To better understand the factors involved in dictating ongoing dynamics in a community at a given time, we must unravel how interactions affect the assembly process. Here, we build a novel, integrative conceptual model for u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 136 publications
(179 reference statements)
4
81
0
1
Order By: Relevance
“…Thébault and Fontaine () have shown that highly connected and nested community architecture promotes stability and resilience in mutualistic interaction networks. Furthermore, the modularity observed in the gut interaction network is a testimony of the stable nature of the gut environment, also associated with mature bacterial communities mostly composed of specialists rather than generalists (Ponisio et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thébault and Fontaine () have shown that highly connected and nested community architecture promotes stability and resilience in mutualistic interaction networks. Furthermore, the modularity observed in the gut interaction network is a testimony of the stable nature of the gut environment, also associated with mature bacterial communities mostly composed of specialists rather than generalists (Ponisio et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Change points analyses were conducted in Python 2.7.10 and R 3.3.2 (R Core Team, 2015). The fully reproducible code and explanations for all analyses is available on GitHub at https:// github.com/lponisio/hedgerow_assembly (Ponisio & Gariarsa 2017).…”
Section: Identifying Change Pointsmentioning
confidence: 99%
“…In addition to the local environment filtering the regional species pool into an assemblage of species capable of persisting in that environment, biotic interactions play an important role in subsequent community assembly (Boulangeat et al 2012;HilleResLambers et al 2012;Kraft et al 2014). Resident species at a local scale therefore reflect the combination of organisms that are selected for the local environment and for local species interactions (HilleResLambers et al 2012;Ponisio et al 2019).…”
Section: Introductionmentioning
confidence: 99%